Exploring the Relationship Between Work Motivation and Job Satisfaction: The Teachers' Perspective in Oman - Ali Sulaiman Talib Al Shuaili (International Journal of Education and Humanities, 2025)
This study explores the relationship between motivation and job satisfaction among schoolteachers in Oman. The study aims to identify how motivation influences teachers' job satisfaction and to uncover the factors affecting both variables. Data were collected through self-administered questionnaires distributed to 680 teachers, followed by descriptive statistical analysis. The results indicated that teachers' motivation and job satisfaction levels were moderate. Additionally, a significant correlation was found between motivation and job satisfaction, suggesting that improving motivation could positively impact teachers' job satisfaction. Critical issues identified in the study include the lack of financial incentives, an unclear system for motivating teacher performance, and insufficient involvement of teachers in school decision-making processes. Based on these findings, the study recommends that the Omani Ministry of Education develop policies and incentives that align with teachers' basic living standards and create a more transparent and participatory system for motivating teachers. Such measures are expected to enhance teacher performance and, ultimately, the quality of education in Oman.